Tinjauan Yuridis Intervensi Pemerintah Selaku Host Country Dalam Memberikan Perlindungan Terhadap Investor Asing di Sektor Perbankan - Veronica, Tri Wanty Octavia (LPPM Universitas Ekasakti Padang, 2024)
Investment in Indonesia is growing in all sectors including banking, capital markets, automotive and others. The banking industry become a major aspect for state development therefore firm implementation of regulation and supervision is needed. Having good banking supervision will encourage economic growth in Indonesia which will be realized by growing investment in other sectors. Normally, Public Officer carried out their supervisory action straight to banking policies, but in some case discretion become one of the alternative to save banking industry from declining financial liquidity. In the other hand, judiciary verdict tend to consider legal positivism only, the following result this banking supervisory action is not permitted. However, the understanding of the tribunal to analize the banking problem should consider the dynamic changes of society. Therefore, the role of the government as Host Country is very important in creating a good investment climate from a judicial perspective which, apart from providing certainty, can also provide justice for foreign investors in Indonesia.